Primary Pelvic Cyst Hydatic - Sayharman, Sema Etiz; Aka, Nurettin; Köse, Gültekin; Tüfekci, Can; Karaca, Kenan (Gynecology Obstetrics & Reproductive Medicine, 2011)
Cyst Hydatic is a human infection caused by Echinococcus larva. The cyst of echinococcus can be seen in every organ and part of the body. Although it is mostly seen in the liver (60%) and in the lungs (15%), it is rarely seen in the genital track. The patient who suffered from abdominal swelling, inguinal pain and anorexia was referred to our emergency policlinic and an abdominal mass was found after the physical examination. The ultrasonographic and computorized tomographic findings suggested a giant mass which had both solid and cystic components and filled the whole pelvis. The patient was operated and diagnosed as Cyst Hydatic peroperatively. The cyst was excised surgically and the abdominal cavity was irrigated by batticon solution in order to prevent recurrences. The diagnosis was supported both by pathologically and serologically (IHA :1/2560).The patient was medically treated by Albendazole (2x2 ) for 6 months. No any pathologic finding was seen after postoperative medical treatment and in 2 years follow up.